Mortality in patients with giant cell arteritis in Spain: results from the ARTESER registry - Juan Molina-Collada; Marta Domínguez-Álvaro; Rafael B. Melero-González; Eugenio de Miguel; Maite Silva-Díaz; Jesús Alejandro Valero Jaimes; Ismael González; Julio Sánchez Martín; Javier Narváez; Joan Calvet; Ivette Casafont-Solé; Jose A Román Ivorra; et al. (Arthritis Research & Therapy)
Abstract Objectives To compare mortality rates between GCA patients and the general population in Spain, and to identify associated factors influencing mortality. Methods ARTESER, a multicenter registry by the Spanish Society of Rheumatology, includes GCA patients from June 2013 to March 2019. Demographic, clinical, imaging, histological and mortality data were collected retrospectively. Only patients with at least one year of follow-up were included for analysis. The mortality rates were expressed as the number of deaths per 1000 person-years, with 95% confidence interval (CI) by sex and age group. Kaplan-Meier method was performed for survival analysis. The factors influencing mortality were analyzed using Cox regression model. Results A total of 1200 patients with GCA were analyzed, with a mean (SD) follow-up of 2.18 (1.53) years. The overall five-year cumulative mortality rate (95%CI) was 37.86 (31.75-43.96) per 1000 patients/year. The cumulative mortality rate was significantly higher in males than females (59.04vs29.06; p<0.001). The age- and sex-adjusted cumulative mortality rate was similar to the Spanish general population (19.75vs20.72;p=0.559). In the multivariate analysis, older age (HR 1.11, 95%CI 1.073-1.142) and male sex (HR 1.775, 95%CI 1.214-2.594) were associated with increased mortality. Headache (HR 0.55, 95%CI 0.362-0.843) and high hemoglobin levels (HR 0.85, 95%CI 0.744-0.970) were protective factors against death. Conclusions The overall five-year age- and sex-adjusted cumulative mortality rate in GCA is similar compared to the general population. Older age and male sex appear to be associated with an increased risk of mortality, whereas headache and high hemoglobin levels might serve as protective factors against death.